Usefulness of the Parent Compound Determination in Bioequivalence Evaluation of Clopidogrel Generic Products - Pawtowska, Monika; Duda, Jolanta; Tejchman-Matecka, Bożena; Monika, Bogiel; Marzec, Adam; Edmund, Sieradzki (Arzneimittelforschung, 2009)
The aim of the presented comparative study was to evaluate the bioavailability of clopidogrel (CAS 113665-84-2) formulations containing clopidogrel bisulfate (CAS 135046-48-9, CBS) 75 mg based on the parent compound (CBS) and its metabolite SR 26334 –clopidogrel carboxylic acid (CAS 144457-28-3, CCA) determination.This paper presents the results of a comparative, randomized, two-way cross-over study on 48 healthy male volunteers assessing the bioequivalence of two products of clopidogrel 75mg in form of film-coated tablets. In each of the two periods, separated by a 7-day washout period, a single dose of 150 mg (2 2 75mg) of test and reference preparations was administered under fasting condition. Nineteen blood samples for determination of CBS and CCA were collected up to 48 h post dose. The CBS and CCA concentrations were quantified by a selective ultra performance liquid chromatographic-tandem mass spectrometric (UPLC-MS/MS) method.Pharmacokinetic parameters such as AUCinf, AUCt, Cmax, t max, t 1/2 were estimated using a non-compartmental model. Bioequivalence evaluation and calculation of CI were performed for clopidogrel and its metabolite by two one-sided t-test procedures by Schuirmann.In case of CCA the values of pharmacokinetic parameters were similar for the two products (test vs reference): AUCinf: 15 773 vs. 15 691 ng · h/mL, AUCt : 15 462 vs. 15 315 ng · h/mL, C max : 4919 vs. 4699 ng/mL, t max : 0.84 vs. 0.93 h, t 1/2: 7.92 vs. 8.41 h. Points of estimation of the ratios test/reference were near to 100% and CI in ranges 80–125% were fulfilled for all tested parameters.Pharmacokinetic parameters values of CBS were: AUCinf : 1.96 vs. 1.84 ng · h/mL (test vs reference), AUCt : 1.91 vs. 1.81 ng · h/mL, C max 1.44 vs. 1.52 ng/mL, t max : 0.90 vs. 0.99 h, t1/2: 0.74 vs. 0.57 h. The parametric 90%-confidence interval (CI) was in the range of 80–125% for AUCt ratio and AUCinf ratio. The CI range of C max fulfilled the widened range of 75–133 % (according to the study protocol). Unfortunately, the very high variability of pharmacokinetic parameters (over 50%) contributed to low power of the test.Measurement of CBS concentrations should not be a reliable one for the bioequivalence assessment, due to very low concentrations, very small and variable values of AUC and high intra-subject variability. Thus, bioequivalence evaluation should be based on CCA determination. In the presented study evaluation based on CCA unequivocally and with the proper power confirmed the bioequivalence between the investigated clopidogrel products.
Keywords: Areplex®; CAS 113665-84-2; CAS 144457-28-3; clopidogrel; clopidogrel carboxylic acid, bioequivalence, pharmacokinetics, UPLC-MS/MS; Platelet aggregation inhibitors